The effects of natural resource extraction on household expenditure patterns: Evidence from Mongolia - Odmaa Narantungalag (Global Labor Organization (GLO), 2022)
This paper investigates the economic impacts of the mining sector on household expenditures. Employing the difference-in-differences model and the Mongolia Household Socio-Economic Survey data from 2008 to 2016, I find that the mining activities benefited local residents. Specifically, mining activities increase household expenditures on food, health, and electricity, respectively, while households reduce their expenditures on education and other non-food items. Interestingly, illness did not increase in the resource-producing region, while educational attainment improved. The findings highlight that the positive impacts of the mining sector are likely to be higher than what is determined by traditional welfare measurements of income and consumption. I provide some anecdotal evidence that the changes in household expenditure patterns can be due to increased availability of health care services and educational facilities in the mining region.
Keywords: L72; O12; O13; Q32; R11; 330; Mining; Natural Resources; Regional Economy; Economic Development